Comprehensive Training of Engineering Students through Continuing Education - Miguel Reynoso Flores; Jaime Arturo Castillo Elizondo; María Isabel Dimas Rangel (Revista Electrónica Educare)
This paper addresses a priority for student training in general and particularly for future engineers. Although this issue has been frequently addressed in recent years, proposals are still insufficient for engineering students. This paper is aimed at theoretically and empirically demonstrating the potential of continuing education as one of the key areas that engineering schools have for the comprehensive training of students. Preliminary results of a research project commissioned by the School of Mechanical and Electrical Engineering (Facultad de Ingeniería Mecánica y Electrica-FIME) of Universidad Autónoma de Nuevo León, Mexico, are presented to respond to the need to improve the learning process of students with a comprehensive approach. The research justification and some of the results obtained in the exploratory phase are also described.